2010
DOI: 10.1159/000321416
|View full text |Cite
|
Sign up to set email alerts
|

Low Lymphocyte Ratio as a Novel Prognostic Factor in Acute Heart Failure: Results from the Pre-RELAX-AHF Study

Abstract: Background: Previous studies have suggested that a lower lymphocyte ratio (Ly%) in the white blood cell (WBC) differential count is related to worse outcomes in patients with acute heart failure (AHF) and other cardiovascular disorders. Methods: In the Pre-RELAX-AHF study, 234 patients with AHF, systolic blood pressure >125 mm Hg and brain natriuretic peptide ≧350 pg/ml or equivalent were randomized to 1 of 4 intravenous doses of relaxin or placebo and followed up for 6 months following randomization. Complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…10 Despite this heterogeneity in study design, similar to our experience, low lymphocyte counts were highly related to known HHF predictors of adverse outcomes. [8][9][10][11] Furthermore, all studies consistently demonstrated that relative lymphopenia was an independent predictor of postdischarge events. [8][9][10][11] Earlier studies are limited because findings were based on relatively small sample sizes and largely single-center experiences.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…10 Despite this heterogeneity in study design, similar to our experience, low lymphocyte counts were highly related to known HHF predictors of adverse outcomes. [8][9][10][11] Furthermore, all studies consistently demonstrated that relative lymphopenia was an independent predictor of postdischarge events. [8][9][10][11] Earlier studies are limited because findings were based on relatively small sample sizes and largely single-center experiences.…”
Section: Discussionsupporting
confidence: 59%
“…[8][9][10][11] Furthermore, all studies consistently demonstrated that relative lymphopenia was an independent predictor of postdischarge events. [8][9][10][11] Earlier studies are limited because findings were based on relatively small sample sizes and largely single-center experiences. The present study represents the largest experience to date to investigate the prognostic role of lymphopenia in the setting of HHF.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Total cholesterol,6 25 albumin8 26 and total lymphocyte count,8 27 have been used as markers of undernutrition with recognised association with morbidity and mortality also in HF.…”
Section: Discussionmentioning
confidence: 99%